2014
DOI: 10.3109/10717544.2014.905651
|View full text |Cite
|
Sign up to set email alerts
|

Bleomycin A6-loaded anionic liposomes with in situ gel as a new antitumoral drug delivery system

Abstract: The goal is to develop an in situ gel system comprising anionic liposomes (AL) containing bleomycin A6 (BLM A6) dispersed within the thermosensitive in situ gel for sustained release. The results indicated that the gelation temperature decreased due to AL within gel. Similarly, viscosity and mechanical parameters, such as gel strength for gel, could be enhanced by inducing lipid material with negative charge (phosphatidylglycerol) at 37 C, which provided against corrosion at physiological condition. The in vit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…The process of formation of in situ hydrogel and sustained release of drugs from the in situ hydrogel into tumor cells was schematically presented in Figure 1. The advantages of an ideal in situ hydrogel as a pharmaceutical preparation can include but not limit to (Cho et al, 2015;Ding et al, 2016;Meng et al, 2019;Zhang et al, 2019): (1) easy to functionalize and clear functional units; (2) biodegradable; (3) good biocompatibility; (4) suitable gelling speed and gel strength; (5) low immunogenicity and toxicity; (6) responsiveness to rapid stimuli from the external environment. With the deepening of researches in related areas, current in situ hydrogels can be divided into pH-, temperature-, ionic strength-, temperature-pH-, and light-sensitive and other types.…”
Section: Types and Characteristics Of In Situ Hydrogelsmentioning
confidence: 99%
“…The process of formation of in situ hydrogel and sustained release of drugs from the in situ hydrogel into tumor cells was schematically presented in Figure 1. The advantages of an ideal in situ hydrogel as a pharmaceutical preparation can include but not limit to (Cho et al, 2015;Ding et al, 2016;Meng et al, 2019;Zhang et al, 2019): (1) easy to functionalize and clear functional units; (2) biodegradable; (3) good biocompatibility; (4) suitable gelling speed and gel strength; (5) low immunogenicity and toxicity; (6) responsiveness to rapid stimuli from the external environment. With the deepening of researches in related areas, current in situ hydrogels can be divided into pH-, temperature-, ionic strength-, temperature-pH-, and light-sensitive and other types.…”
Section: Types and Characteristics Of In Situ Hydrogelsmentioning
confidence: 99%
“…Bleomycin A6 (BLM A6) is a glycopeptide produced by the bacterium Streptomyces verticillus, characterized by antibiotic and antitumoral activity [72]. It acts by means of DNA cleavage through the production of reactive oxygen species following complexation with Fe 2+ ions [100].…”
Section: Biocompatible Nanocarrier-loaded Poloxamer 407 Hydrogelsmentioning
confidence: 99%
“…However, high and frequent doses of BLM A6 are required due to its short half-life and fast clearance [101]. The goal of Ding and coworkers was to develop an anionic liposomal formulation containing BLM A6 that was dispersed in a thermo-sensitive P407 hydrogel in order to prolong the release rate of the drug and its pharmacological efficacy [72]. The negative charge (due to the phosphatidylglycerol) of the surfaces of the vesicles enhanced viscosity and gel strength at 37 °C, avoiding the rapid corrosion of the polymeric matrix under physiological conditions and in vivo fluorescence imaging performed on Kumming mice demonstrated that this formulation remained at the administration site for at least five days [72].…”
Section: Biocompatible Nanocarrier-loaded Poloxamer 407 Hydrogelsmentioning
confidence: 99%
“…BLM shows bone-marrow suppression to only a slight degree, which is a typical adverse effect of general anticancer drugs, but administration of BLM causes other adverse effects such as interstitial pneumonia, lung fibrosis, pyrexia, and emesis [38,39,40]. To improve the bioavailability of BLM and to decrease its adverse effects, BLM-conjugated gold nanoparticles, magnetic nanoparticles, nanogels, and liposomes have been reported [41,42,43,44,45,46,47]. Although folate-PEG-modified liposomes achieved targeted delivery to tumor cells via folate receptor-mediated endocytosis and tumor inhibition in vivo, BLM release behavior from liposomes was slow: 50% of BLM was retained in liposomes even after incubation at acidic pH for 36 h [47].…”
Section: Introductionmentioning
confidence: 99%